The Relationship of the Cardiovascular System Health With Demensia at the Age of 50-60 Years at Haji General Hospital - Zaim Anshari (International Journal of Public Health Excellence (IJPHE), 2022)
Dementia is a syndrome in which there is a decline in memory, thinking, behavior and ability to carry out daily activities. Several studies have shown a link between the development of cognitive impairment and dementia and educational attainment, and lifestyle-related risk factors, such as physical inactivity, tobacco use, unhealthy diet and harmful use of alcohol. Dementia can be identified using the MMSE ( Mini Mental State Examination ). Furthermore, certain medical conditions are associated with an increased risk of developing dementia, including hypertension, diabetes, dyslipidemia, obesity and depression. The ideal cardiovascular health score, also referred to as Life's Simple 7, consists of four health behavior indicators, and three biologics. analysis using a cross-sectional design , which was carried out at the Hajj Hospital, December 2020 - March 2021 and involved 70 respondents. Data obtained by medical records and interviews. Based on the results of the study, the results of the somer's d correlation test obtained a value of p = 0.000 (p <0.05) so that a significant relationship was found between the Health of the Cardiovascular System and the Incidence of Dementia at the Age of 50-60 Years . There is a relationship between the health of the cardiovascular system and the incidence of dementia at the age of 50-60 years.